Activation of the Cholinergic Anti-Inflammatory Pathway as a Novel Therapeutic Strategy for COVID-19 - Qin, Zhen; Xiang, Kefa; Su, Ding-Feng; Sun, Yang; Liu, Xia (Frontiers in Immunology, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) underlined the urgent need for alleviating cytokine storm. We propose here that activating the cholinergic anti-inflammatory pathway (CAP) is a potential therapeutic strategy. However, there is currently no approved drugs targeting the regulatory pathway. It is evident that nicotine, anisodamine and some herb medicine, activate the CAP and exert anti-inflammation action in vitro and in vivo. As the vagus nerve affects both inflammation and specific immune response, we propose that vagus nerve stimulation by invasive or non-invasive devices and acupuncture at ST36, PC6, or GV20, are also feasible approaches to activate the CAP and control COVID-19. It is worth to investigate the efficacy and safety of the strategy in patients with COVID-19.